The Marketing Strategies of the Thai Rice Business in Xi’an City，Shaanxi Province , China - Yang, JingXin; Raoprasert, Tanachart; Sihabutr, Chaturaporn (Journal of International Buddhist Studies, 2018)
Thai rice positioned as a high-end imported product which faced many matters during selling process in Xi’an City. Marketing strategy had a crucial impact on long-term survival and development of enterprises. This study aimed to found which factor will influence the marketing strategy in Thai rice business as marketing mix as research variables. The data used structured interview technique on six interviewees who expert in Thai rice business from four successful enterprises in Xi’an. The study results showed that four factors played different roles in marketing strategy and for Thai rice business, “place” had highest impact on strategy planning, because place directly related to the speed and area of the product into the market. Followed by “product” which was the basic of the trade, the symbol of corporate image and brand. Then showed the contradictory opposition on“promotion” and “price”.